PROPERTIES AND MODIFICATION METHODS OF HALLOYSITE NANOTUBES: A STATE-OF-THE- ART REVIEW - Jawwad Saif, Muhammad; Muhammad Asif, Hafiz; Naveed, Muhammad (Journal of the Chilean Chemical Society, 2018)
The halloysite nanotubes (HNTs) are naturally found in New Zealand, China, Brazil, America, and France. Halloysite nanotubes have unique physical, chemical, and electrochemical properties. Due to their non-hazardous nature and easy availability, they are used in various fields of science. To improve halloysite nanotubes’ interactions, these can be functionalized by different modification methods like covalent functionalization, non-covalent functionalization, etc. The chemical formula of halloysite nanotubes is Al2Si2O5(OH)4.2H2O. HNTs have a nanotubular geometry which exhibit its dimensions on nanoscale. This nanotubular array of HNTs varies with different regions. In this review, we have tried to reiterate the key properties and various methods to modify halloysite nanotubes.